A role for LHC1 in higher order structure and complement binding of the Cryptococcus neoformans capsule. - Yoon-Dong Park; Soowan Shin; John Panepinto; Jeanie Ramos; Jin Qiu; Susana Frases; Patricia Albuquerque; Radames J B Cordero; Nannan Zhang; Uwe Himmelreich; David Beenhouwer; John E Bennett; et al. (PLoS Pathogens)
Polysaccharide capsules are important virulence factors for many microbial pathogens including the opportunistic fungus Cryptococcus neoformans. In the present study, we demonstrate an unusual role for a secreted lactonohydrolase of C. neoformans, LHC1 in capsular higher order structure. Analysis of extracted capsular polysaccharide from wild-type and lhc1Δ strains by dynamic and static light scattering suggested a role for the LHC1 locus in altering the capsular polysaccharide, both reducing dimensions and altering its branching, density and solvation. These changes in the capsular structure resulted in LHC1-dependent alterations of antibody binding patterns, reductions in human and mouse complement binding and phagocytosis by the macrophage-like cell line J774, as well as increased virulence in mice. These findings identify a unique molecular mechanism for tertiary structural changes in a microbial capsule, facilitating immune evasion and virulence of a fungal pathogen.